Application of massive 3D head and facial scan datasets in ergonomic head-product design. (2016) - Lee, Wonsup; Yang, Xiaopeng; Jung, Hayoung; You, Heecheon; Goto, Lyè; Molenbroek, Johan F.M.; Goossens, Richard H.M.
3D human body scan datasets have been collected and various techniques of post-processing, size and shape analysis, and applications in product design have been introduced. This paper is aimed to introduce techniques and cases of head-product design studies based on massive 3D head scan datasets. 3D scan datasets of the head, face and ear were collected and post-processed by editing, landmarking, alignment and measurement. For useful application of the 3D head scan datasets in head-product designs, we applied several analysis techniques such as development of a sizing system, selection of representative models, analysis of shape variation based on template-registered 3D scans and analysis of virtual fit. This paper can help understand an overview of techniques regarding massive 3D scan datasets and their applications to ergonomic product design.